Public employment and political pressure: The case of French hospitals - Andrew E. Clark; Carine Milcent (Institute for the Study of Labor (IZA), 2010)
This paper uses an unusual administrative dataset covering the universe of French hospitals to consider hospital employment: this is consistently higher in public hospitals than in Not-For-Profit (NFP) or private hospitals, even controlling for a number of measures of hospital output. NFP hospitals serve as a benchmark, being very similar to Public hospitals, but without political influence on their hiring. Public-hospital employment is positively correlated with the local unemployment rate, whereas no such relationship is found in other hospitals. This is consistent with public hospitals providing employment in depressed areas. We appeal to the Political Science literature and calculate local political allegiance, using expert evaluations on various parties' political positions and local election results. The relationship between public-hospital employment and local unemployment is stronger the more left-wing the local municipality. This latter result holds especially when electoral races are tight, consistent with a concern for re-election.
Keywords: D21; D72; I18; J21; 330; Hospitals; public employment; unemployment; political preferences; Krankenhaus; Personalbestand; Kommunales Unternehmen; Öffentlicher Dienst; Regionale Arbeitslosigkeit; Parteipolitik; Public Choice; Frankreich